PENGARUH INFLUENCER REVIEW DAN CUSTOMER REVIEW TERHADAP PURCHASE INTENTION PADA PRODUK AVOSKIN - Clarissa Safira Maharani; Tri widarmanti (Serat Acitya, 2022)
The development of internet technology in the current era of globalization has had a significant impact on the world of business and the economy. The use of internet technology in business has increased marketing reach, transaction speed, and speed of delivery of goods and services. This is shown by the large number of offers for beauty and body care product categories on e-commerce platforms. The beauty industry notes that ways to promote and encourage product purchase transactions are influenced by eWOM communications, one of which is customer reviews and influencer reviews. The purpose of this study was to measure the direct effect of eWOM, including customer reviews and influencer support, on purchase intentions for Avoskin products, with trust as a moderator variable. The method used in this research is a quantitative method of causal research. The sampling technique in this study was non-probability sampling and the method used was convenience sampling with 400 respondents. This study used a questionnaire data collection technique with an ordinal scale and used data analysis techniques (PLS-SEM). The results of this study conclude that customer reviews have a significant positive effect on purchase intention of Avoskin products, influencer reviews do not have a significant positive effect on purchase intentions of Avoskin products, trust negatively moderates the relationship between customer reviews on purchase intention of Avoskin products and trust does not moderate the relationship between influencer reviews and purchase intention of Avoskin products.